Panama : Assessment of Financial Sector Supervision and Regulation, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Insurance Supervision, and Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Assessment of Financial Sector Supervision and Regulation for Panama. The assessment of bank supervision showed a high degree of compliance with the Basel Core Principles (BCP) reflecting generally satisfactory implementation combined with an adequate legal and regulatory foundation. The supervisory and regulatory frameworks for capital markets and insurance sectors are underdeveloped. The securities law and regulations are generally effective; however, resources for securities markets oversight are insufficient, and independence is affected by unfilled positions, including a commissioner's post.